Lyophilized human platelet lysate: manufacturing, quality control, and application - Wendland, Kerstin; Koblin, Lea; Stobbe, Dirk; Dahms, Anna; Singer, Debora; Bekeschus, Sander; Wesche, Jan; Schoon, Janosch; Aurich, Konstanze (Frontiers in Cell and Developmental Biology, 2025)
BackgroundA significant number of platelet concentrates (PCs) is discarded daily in blood banks due to limited shelf life. Human platelet lysate (HPL), derived from expired PCs, has gained attention as an ethical and sustainable cell culture media supplement in biomedical research and cell therapy production. However, HPL is subject to decisive disadvantages such as batch differences and lack of storage stability. To overcome these limitations and to enhance the applicability of HPL, we developed an HPL manufacturing protocol including a lyophilization process. The aim of this study was to investigate the influence of HPL lyophilization on parameters of quality control, including growth factor concentrations and the culture of human mesenchymal stromal cells (hMSCs).MethodsWe performed a paired comparison of six batches of HPL and lyophilized HPL (L-HPL) regarding the quality parameters pH, total protein, osmolality, sodium, potassium and chloride concentration. Concentrations of 11 growth factors and cytokines were compared between HPL and L-HPL. Additionally, we determined cell yield, proliferation capacity, viability and trilineage differentiation potential of hMSCs following expansion in HPL- and L-HPL-supplemented cell culture media.ResultsQuantification of the quality parameters revealed non-altered pH, osmolality and potassium concentrations and slightly lower total protein, sodium and chloride concentrations of L-HPL compared to HPL. Growth factor and cytokine concentrations did not differ between HPL and L-HPL. Cell yield, division cycles and viability of hMSCs cultured in either HPL- or L-HPL-containing media were comparable. Cells differentiated in medium containing L-HPL showed a slightly higher capacity for osteogenic differentiation, while adipogenic differentiation and chondrogenic differentiation potentials remained unchanged.ConclusionWe successfully developed a method to produce well-applicable L-HPL. The comparison of L-HPL with HPL did not reveal any relevant differences regarding quality control parameters of routine testing, growth factor concentrations and hMSC functionality, demonstrating the suitability of L-HPL as a cell culture supplement. These results emphasize the potential of L-HPL as a sustainable and ethical alternative to animal-derived serum products in biomedical research and drug development.